Frizzled 2 Functions in the Regulation of TOR-Mediated Embryonic Development and Fecundity in Cyrtorhinus lividipennis Reuter - Ge, Linquan; Jiang, Lu; Zheng, Sui; Zhou, Yongkai; Wu, Qing; Liu, Fang (Frontiers in Physiology, 2020)
The mirid bug, Cyrtorhinus lividipennis Reuter, is an important predator of rice planthoppers in Asia. In a previous study, C. lividipennis fed on gramineous weeds had reduced development compared to those fed on rice. In the current study, the concentrations of selected amino acids (AAs) were higher in rice than five gramineous species, which might explain the enhanced growth of C. lividipennis on rice. When C. lividipennis was fed on AA-deprived artificial diets, the Wnt/β-catenin pathway was inhibited. Furthermore, C. lividipennis females silenced for expression of Fz2 showed a significant reduction in the Wnt/β-catenin and target of rapamycin (TOR) pathways. Silencing Fz2 led to decreased expression of the vitellogenin gene (Vg), lower Vg accumulation in oocytes, reduced soluble protein in ovaries and fat bodies, reduced titers of juvenile hormone, prolonged preoviposition periods, and lower predation capacity, body weight, and egg numbers as controlled to controls. Fz2 silencing resulted in undeveloped ovaries and the inhibition of oocyte growth in the ovarioles, resulting in decreased numbers of offspring and reduced hatching rates. The silencing of Fz2 also resulted in aberrant embryos with undeveloped eyespots and organs, suggesting that Fz2 is essential gene for embryonic development, oogenesis and egg maturation. In summary, this study established a direct link between Wnt and TOR pathways, which interact synergistically to regulate C. lividipennis reproduction in response to AA signals. These results provide valuable new information that can be applied to large-scale rearing of C. lividipennis predators, which is important for reducing planthopper damage in rice fields.